FIA- spectrophotometric method for the determination of amoxicillin in pharmaceuticals; application of AES, GAPI, and AGREE greenness assessment tools - Marwa sabbar Falih; Ruba Fahmi Abbas; Neda Ibrahim Mahdi; Nisreen Kais Abood; Mohammed Jasim M Hassan (MethodsX, 2023)
A new, simple, and sensitive FIA-spectrophotometric method has been developed for evaluating pure amoxicillin and pharmaceutical formulations. The FIA method involves the reaction of dapsone with sodium nitrite and hydrochloric acid. Subsequently, the diazotized dapsone is coupled with amoxicillin in an alkaline medium, resulting in a stable orange dye with a maximum wavelength of 440 nm. The developed method was validated according to the ICH guidelines and found to have a concentration range of 1–150 µg/mL, a correlation coefficient of 0.9994, a molar extinction coefficient of 0.273 × 104 L/mol.cm, and a detection limit of 0.074 µg/mL. The FIA method was then evaluated using AES, GAPI, and AGREES analytical greenness assessment tools. The FIA method uses dapsone as an eco-friendly reagent, in addition to the FIA method's advantages of reduced sample and reagent usage, reduced waste generation, and cheaper equipment. So, it has been proposed as an excellent eco-friendly method for the determination of AMX in pharmaceutical formulations.